Degradable intake protein supplementation through the inclusion of urea in finishing diets containing distillers grains: effects on feedlot cattle performance, ruminal fermentation, and feed digestibility - Ceconi, Irene (2014)
Tesis para obtener el grado de Philosophical Doctor (PhD), Major: Animal sciences, de la University of Minnesota, en mayo de 2014